2022
DOI: 10.1097/wco.0000000000001090
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in establishing a cure for GNE myopathy

Abstract: Purpose of review GNE myopathy is a rare autosomal recessive disease caused by biallelic variants in the GNE gene, which encodes an enzyme involved in sialic acid biosynthesis. No drugs are approved for the treatment of GNE myopathy. Following proof-of-concept of sialic acid supplementation efficacy in mouse models, multiple clinical trials have been conducted. Here, we review clinical trials of sialic acid supplementation therapies and provide new insights into the additional clinical features of GNE myopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Although there are no significant therapeutic drugs approved for Nonaka myopathy, trials for several potential therapeutic tools, including sialic acid supplementation and gene therapy, are currently in progress [6,50]. Long-term safety was assessed for ManNAc, which may provide preliminary evidence for clinical efficacy [51].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no significant therapeutic drugs approved for Nonaka myopathy, trials for several potential therapeutic tools, including sialic acid supplementation and gene therapy, are currently in progress [6,50]. Long-term safety was assessed for ManNAc, which may provide preliminary evidence for clinical efficacy [51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Neu5Ac extended-release formulation therapies helped GNE myopathy patients ameliorate the decline in upper extremity muscle strength [ 65 ]. GNE myopathy, arising from variants in gene GNE , is a kind of neuromuscular disease.…”
Section: Applications Of Neu5acmentioning
confidence: 99%
“…2017 ). A current review of clinical trials to treat GNEM patients can be found here ( Yoshioka et al. 2022 ).…”
Section: Introductionmentioning
confidence: 99%